The whispering house - Wade, Rebecca (Katherine Tegen Books, 2012)
When the Price family moves into Cowleigh Lodge while their home is being repaired, fourteen-year-old Hannah discovers that the ghost of a girl who died there at age eleven wants help unraveling the mystery of her 1877 death.